Implementasi Pengungkapan Perkara Tindak Pidana Penyertaan Dalam Pencurian Dengan Pemberatan Di Kepolisian Sektor Kempas (STUDI PERKARA NOMOR: LP/B/08/IX/2025/SPKT/POLSEK.KEMPAS) - Wahyono; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
The crime of complicity in aggravated theft involves more than one offender and requires an effective case disclosure process by the police. This study aims to examine the implementation of case disclosure in criminal acts of complicity in aggravated theft at the Kempas Sector Police based on Case Number: LP/B/08/IX/2025/SPKT/POLSEK.KEMPAS, as well as to identify the obstacles encountered and the efforts made by investigators. This research employs an empirical legal method with an empirical juridical approach. Data were collected through interviews, library research, and documentation, and analyzed using descriptive qualitative methods. The findings indicate that the case disclosure process has been carried out in accordance with applicable legal provisions through investigation, inquiry, evidence collection, examination of witnesses and suspects, and case file preparation. The main obstacles include limited evidence, fugitives, and insufficient public cooperation. Efforts undertaken include strengthening coordination, optimizing investigative measures, and enhancing community participation.